2013
DOI: 10.1111/ecin.12028
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the Scientific Productivity of Highly Productive Economists

Abstract: This paper studies the evolution of research productivity of a sample of economists working in the best 81 departments in the world in 2007. The main novelty is that, in so far as a productivity distribution can be identified with an income distribution, we measure productivity mobility in a dynamic context using an indicator inspired in an income mobility index suggested by Fields (2010) for a two-period world. Productivity is measured in terms of publications, weighted by the citation impact of the journals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
(74 reference statements)
0
10
0
1
Order By: Relevance
“…Although highly productive academic scientists are rarely scrutinised as a separate segment of the academic profession, scientific productivity is skewed, and this skewness has been widely studied using two standard measures of individual performance: number of publications and number of citations (Albarrán, Crespo, Ortuño, & Ruiz‐Castillo, ; Carrasco & Ruiz‐Castillo, ). In their study of 17.2 million authors and 48.2 million publications in Web of Science, Ruiz‐Castillo and Costas () found that 5.9 per cent of authors accounted for about 35 per cent of all publications.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Although highly productive academic scientists are rarely scrutinised as a separate segment of the academic profession, scientific productivity is skewed, and this skewness has been widely studied using two standard measures of individual performance: number of publications and number of citations (Albarrán, Crespo, Ortuño, & Ruiz‐Castillo, ; Carrasco & Ruiz‐Castillo, ). In their study of 17.2 million authors and 48.2 million publications in Web of Science, Ruiz‐Castillo and Costas () found that 5.9 per cent of authors accounted for about 35 per cent of all publications.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…6 We select countries and departments in four steps. 7 We begin with a dataset used in previous contributions (Carrasco and Ruiz-Castillo 2014;Albarrán et al 2017a, b), consisting of the top 81 Economics departments worldwide according to the Econphd (2004) ranking. We aim to select a minimum of five or six departments for large European countries and important cases, such as Canada, and a minimum of two departments for any other country.…”
Section: The Selection Of Sample Countries and Departmentsmentioning
confidence: 99%
“…However, the Scopus dataset for the last 22 years is both authoritative and comprehensive, and the same criticism can be raised for other datasets.  The focus is on past (retrospective) real performance rather than on future expected (prospective) performance (Carrasco & Ruiz-Castillo, 2014;Chang et al, 2011), and it does not account for the life cycles of articles. However, using impact factors would require a reliance on debatable information, such as the 2-year vs. 5-year impact factors described by Sangwal (2013), from a dispersed and always in-progress dataset, as in the case of the temporal evolution of impact factors that is discussed by Finardi (2013).…”
Section: Discussionmentioning
confidence: 99%